Patients with lichen sclerosus experience moderate satisfaction with treatment and impairment of quality of life: results of a cross‐sectional study. (21st March 2017) - van Cranenburgh, O.D.; Nijland, S.B.W.; Lindeboom, R.; de Korte, J.; de Rie, M.A.; ter Stege, J.A.; Prinsen, C.A.C.
Summary: Background: Although they are considered relevant, little is known about satisfaction with treatment and health‐related quality of life (HRQoL) among patients with lichen sclerosus (LS). Objectives: In a cross‐sectional study, we aimed to examine (i) satisfaction with treatment, (ii) patient characteristics associated with satisfaction and (iii) HRQoL in Dutch patients with LS. Methods: Members of the Dutch LS Patient Association ( n = 750) were invited to complete a web‐based survey. We measured satisfaction with treatment with a study‐specific questionnaire, and HRQoL with the Skindex‐29. We calculated domain scores for symptoms, emotions and functioning, and categorized scores into little, mildly, moderately or severely impaired HRQoL. We used a multiple linear regression analysis to examine whether patient characteristics were associated with treatment satisfaction. Results: In total 303 patients (40·4%) were included. Patients under current treatment ( n = 265, 87·5%) were moderately satisfied with their treatment. Patients rated 'treatment effectiveness' as most important, although 58 (22%) were dissatisfied with the effectiveness of their current treatment. More impairment on the HRQoL emotions domain and a higher degree of disease severity were both associated with lower satisfaction with treatment and explained in total 13·5% of the variance in treatment satisfaction. On all HRQoL domains, one‐third of the patients (range 34·7–38·9%) reported severe impairment. Conclusions: Patients with LS are moderately satisfied with their treatment, and one‐third of patients experience severe impairment of HRQoL. To improve dermatological care, we recommend enhancement of doctor–patient communication, information provision and organization, which may be more amenable to change than treatment effectiveness or safety. Abstract : What's already known about this topic? Patients' satisfaction with treatment is an important indicator of quality of care. Little is known about patients' satisfaction with treatment of lichen sclerosus (LS). LS appears to have a negative impact on health‐related quality of life (HRQoL). What does this study add? Patients with LS are moderately satisfied with their current treatment. Patients with LS are least satisfied with the effectiveness of their treatment, but do rate it as most important. One‐third of patients with LS experience severe impairment of HRQoL (symptoms, emotions and functioning domains of Skindex‐29). More impairment on the emotions domain and a higher degree of disease severity are both associated with lower satisfaction with treatment. What are the clinical implications of this work? To improve dermatological care, we recommend enhancement of doctor–patient communication, information provision and organization. In daily clinical practice, we recommend recurrently to assess satisfaction and HRQoL in patients with LS, in addition to clinical measures. Routine measurement of patient‐reported outcomes in daily practice may be facilitated by a web‐based application, but implementation of such an intervention is not self‐evident. Respond to this article Linked Comment:Dizon and Chren. Br J Dermatol 2017; 176:1431–1432 Plain language summary available online